PENGARUH NET INTEREST MARGING (NIM) DAN BEBAN OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) TERHADAP PERTUMBUHAN LABA PADA PT BANK MASPION INDONESIA TBK PERIODE 2013-2022 - Farikha Aulya Maulidina; Gatut Dradjad Purwoko (Journal of Research and Publication Innovation, 2025)
This study aims to determine the Effect of Net Interest Margin (NIM) and Operating Expenses on Operating Income (BOPO) on Profit Growth and both partially and simultaneously in PT Bank Maspion Indonesia Tbk for the 2013-2022 Period. This study uses a quantitative research method that is descriptive. The selected population is the Financial Statements of PT Bank Maspion Indonesia Tbk and the sample used for the financial position statement (balance sheet) and profit and loss statement for the period 2013-2022. The data analysis techniques used were calculating the results of each variable, descriptive statistical test, classical assumption test, multiple regression analysis, correlation coefficient analysis, hypothesis test and determination coefficient test. Based on the results of the partial study using the t-test, NIM did not have a significant influence on Profit Growth with a significance value of 0.685 > 0.05 with a t-value of 0.423 < t table 2.306. The results of BOPO's research prove that there is no negative influence on Profit Growth with a significance value of 0.360 > 0.05 with a t-value of -0.979 < t table 2.306. The results of the simultaneous NIM and BOPO tests had no effect on Profit Growth with a significance value of 0.597 > 0.05 with an F valueof 0.557 < Ftable 4.74. The determination coefficient shows a value of 0.137 or 13.7%, so it can be concluded that the level of relationship between the NIM and BOPO variables has a very low contribution to Profit Growth of 13.7% while 86.3% is influenced by other variables that are not studied in this study.